2007
DOI: 10.1113/expphysiol.2007.039750
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydralazine on the pulmonary vasculature and respiratory control in humans

Abstract: This study sought: (1) to clarify the effects of hydralazine on both the pulmonary vasculature and respiratory control in euoxia and hypoxia in healthy humans; and (2) to determine whether hydralazine alters the expression of genes regulated by hypoxia-inducible factor 1 (HIF-1). Ten volunteers participated in two 2 day protocols. Hydralazine (25 mg) or placebo was administered at 1 pm and 11 pm on the first day, and at 1 pm on the second day. In the mornings and afternoons of both days, we measured plasma vas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Since hydralazine induces vascular smooth muscle (VSM) relaxation via multiple mechanisms [31,32,33], the pathways by which it affects remodeling and activation of tone are not known. Moreover, recent studies have demonstrated that hydralazine augments flow-induced remodeling through a mechanism linked to reactive oxygen species [34].…”
Section: Discussionmentioning
confidence: 99%
“…Since hydralazine induces vascular smooth muscle (VSM) relaxation via multiple mechanisms [31,32,33], the pathways by which it affects remodeling and activation of tone are not known. Moreover, recent studies have demonstrated that hydralazine augments flow-induced remodeling through a mechanism linked to reactive oxygen species [34].…”
Section: Discussionmentioning
confidence: 99%